Flood Rate Assessment of the Woyla River Watershed, Aceh Province, Indonesia - Rifa Alayani; Sugianto Sugianto; Hairul Basri (Graduate Program of Syiah Kuala University, 2021)
This study aims to assess Flood susceptibility and flood hazard levels and obtain the distribution of hazard levels and flood hazards in the Woyla watershed, Aceh Province. This research design generally uses a descriptive survey method and divide into several stages, such as data collection, data processing, data presentation, and delivery of research results. Each determinant of flood-prone areas includes a land slope, altitude, soil texture, drainage, land cover, and rainfall, analyzed spatially utilizing a map. Furthermore, based on the map, the regions are described based on the values that have been divided into classes. The results showed that the level of flood vulnerability in the Woyla watershed was divided into five classes, namely; the non-vulnerable class with an area of 14.88 Ha / 0.01%, low prone with an area of 90,731.62 Ha / 35.45%, medium with an area of 57,120.35 Ha / 22.32%, high with an area of 44,918.15 Ha / 17.55%, and very high with an area of 63,151.72 Ha / 24.67%. Also obtained a map of the distribution of flood hazard areas, the Woyla watershed area is divided into five classes, namely; the very light class with an area of 179,146.15 Ha / 70.00%, mild with an area of 32,868.84 Ha / 12.84%, moderate with an area of 20,129.93 Ha / 7.87%, danger with an area of 6.007. 29 Ha / 2, 35%, and very dangerous with an area of 17,784.51 Ha / 6.95%. The level of flood vulnerability in the Woyla watershed is dominant in West Aceh Regency, which is in the very high and high category classes with a total area of 56,876.65 Ha and 23,527.40 Ha. Meanwhile, the level of flood hazard in the Woyla watershed is also more dominant in West Aceh Regency than falls into the most dangerous and dangerous class category with a total area of 17,784.51 Ha and 6,007.29 Ha. With the largest part in the very light class at the flood hazard level of 179,146.15 ha.